1994
DOI: 10.1107/s0907444994002556
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of hemoglobins II and III of the symbiont-harboring clam Lucina pectinata

Abstract: Diffraction data to 2.7 A resolution were measured on crystals of the homotetramers of components II and III of the cytoplacmic hemoglobin of the symbiont-harboring clam Lucina pectinata. Even though the crystallization conditions are different and the sequence homology of the two hemoglobins is only 63%, the crystals are isomorphous to each other and to the heterotetramer Hb II/III, implying that the residues primarily involved in the intermolecular interactions and responsible for crystal cohesion may be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Initial crystallization conditions were screened using the 24-condition Crystallization Screening Kit (GCB-CSK; Triana Science and Technology) adapted from the mini-screen described by Kimber & Vallee (2003). As previously observed during crystallization experiments of HbII using vapour diffusion (Kemling et al, 1991;Doyle et al, 1994) and counterdiffusion techniques (Gavira et al, 2006) Representative crystals of oxyHbII obtained in sodium formate at (a) pH 4, (b) pH 5, (c) pH 8 and (d) pH 9. (Ruiz-Martínez et al, 2009) a large number of hits were obtained (11 conditions), but only those crystals grown in the presence of sulfate or formate were of good optical quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial crystallization conditions were screened using the 24-condition Crystallization Screening Kit (GCB-CSK; Triana Science and Technology) adapted from the mini-screen described by Kimber & Vallee (2003). As previously observed during crystallization experiments of HbII using vapour diffusion (Kemling et al, 1991;Doyle et al, 1994) and counterdiffusion techniques (Gavira et al, 2006) Representative crystals of oxyHbII obtained in sodium formate at (a) pH 4, (b) pH 5, (c) pH 8 and (d) pH 9. (Ruiz-Martínez et al, 2009) a large number of hits were obtained (11 conditions), but only those crystals grown in the presence of sulfate or formate were of good optical quality.…”
Section: Resultsmentioning
confidence: 99%
“…The first HbII crystallization condition was obtained using the hanging-drop vapour-diffusion method. The crystallization condition employed was 8% saturated ammonium sulfate solution and 50 mM Tris-HCl pH 7, using protein at 1.9 mM in 50 mM phosphate buffer pH 7.5 and 0.05 mM EDTA (Doyle et al, 1994;Kemling et al, 1991). Another crystallization condition was obtained in a 0.2 mm capillary containing 0.1%(w/v) agarose using a lyophilized HbII sample dissolved in 50 mM bis-tris propane buffer pH 7 with 0.5 mM EDTA.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of haemoglobin I from L. pectinata was solved more than 10 y ago (Rizzi et al, 1994(Rizzi et al, , 1996, but the structures of haemoglobin II and III remain unsolved, although preliminary crystal-lization data were reported in 1991 (Kemling et al, 1991) and 1994 (Doyle et al, 1994). Here, we report the crystallization and the first crystallographic data of haemoglobin II from the clam L. pectinata.…”
Section: Introductionmentioning
confidence: 90%
“…[ 11 ] Later, crystallographic results of the HbII and HbIII homodimer complexes concluded that the crystals were isomorphous, diffracted to 2.7 Å, and contained a dimer in the asymmetric unit. [ 12 ] Gavira et al . employed a capillary counter‐diffusion technique for Oxy(HbII‐HbII) to obtained crystals and reported the crystallographic structure at 1.9 Å resolution [ 13 ] (PDB ID 2OLP).…”
Section: Introductionmentioning
confidence: 99%